Desempenho das start-ups/tic e as contribui????es das aceleradoras: um estudo de caso - Fernandes, J??lio Reinaldo da Costa (2015)
This research aims to identify how the accelerators??? can collaborate with the performance of an accelerated start-up/ICT and identify the facilitators factors for the performance achieved. They also sought to identify the achievements of the company accelerated after participation in the acceleration program. With qualitative and exploratory approach, this is a single case study conducted in a start-up/ICT choice for adherence to the research objectives. The research showed that not all services offered by the accelerator, as raised in the theoretical framework, were present in the acceleration of the company studied process, and that the services offered during acceleration had different contributions to the company's performance in the opinion of their entrepreneurs. The factors evaluated by the best for the company's performance were the mentoring, the demo-day and the networking. The results showed that the process of acceleration contributed to the increased speed in product development, to define the roles of each partner in the enterprise and to the perception of possible new customer segments. The start-up/ICT, after completing the process of acceleration, achieved revenue growth, growth in numbers of customers and employees and surpassed the three-year survival.